Molecular cloning and expression of a cold-adapted lipase gene from an antarctic deep sea psychrotrophic bacterium Pseudomonas sp. 7323 - Zhang, Jin-Wei; Zeng, Run-Ying (Marine Biotechnology, 2008)
This is the author accepted manuscript. The final version is available from Springer via the DOI in this record . A psychrotrophic bacterium producing a cold-adapted lipase was isolated from the deep-sea sediment of Prydz Bay, Antarctic and identified as a Pseudomonas strain. Determination of the nucleotide sequence of the gene encoding a lipase from Pseudomonas sp. 7323 (lipA) revealed that LipA is composed of 617 amino acid residues with a calculated molecular weight of 64,466 Da. LipA has a GXSXG motif, which is conserved in lipases/esterases and generally contains the active-site serine. The lipase purified from the Escherichia coli transformant (rLipA) by metal-chelating chromatography exhibited the same electrophoretic mobility as did the wild-type lipase (wLipA) purified from strain 7323, and both enzymes were quite similar in physicochemical properties. The optimal temperature and pH value for the lipases activity were 30°C and 9.0, respectively. They were unstable at temperatures above 25°C and only retained half of their highest activity after incubation at 60°C for 5 min. These results indicated that the enzymes were typical alkaline cold-adapted enzymes. Both enzymes were particularly activated by Ca2+. Additionally, the enzymes hydrolyzed p-nitrophenyl caprate and tributyrin at the highest velocity among the other p-nitrophenyl esters and triglycerides. Hi-Tech research and development program of China